Application of Physical Sciences Scientific Language Register in Tshivenḓa to Shape Meaningful Learning - Madavha, Mpho Kenneth; Ntuli, Thuli Gladys; Mudau, Awelani Victor (Research in Social Sciences and Technology- OpenED Network, 2025)
This study employed a qualitative interpretative case study methodology, involving two teachers and one class of learners from two selected schools. The researcher used observation to address a critical question: How does the application of the Tshivenḓa scientific language register shape meaningful learning? The findings reveal that the application of the Tshivenḓa scientific language register in classrooms fosters interactive and meaningful learning experiences compared to when English is used. Therefore, this study recommends conducting further research and collaboration to develop a comprehensive Tshivenḓa scientific language register with standardized terminology. This would require input from linguists, educators, and other relevant stakeholders to ensure accuracy and consistency.